2020
DOI: 10.3390/ijerph17041403
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Weather Variables on Mosquito Activity: A Snapshot of the Main Point of Entry of Cyprus

Abstract: Mosquitoes are vectors of pathogens, causing human and animal diseases. Their ability to adapt and expand worldwide increases spread of mosquito-borne diseases. Climate changes contribute in enhancing these “epidemic conditions”. Understanding the effect of weather variables on mosquito seasonality and host searching activity contributes towards risk control of the mosquito-borne disease outbreaks. To enable early detection of Aedes invasive species we developed a surveillance network for both invasive and nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…increased (Ciota et al, 2014). Drakou et al (2020) reported that temperature affects host searching activity of Cx. pipiens, Ae.…”
Section: Introductionmentioning
confidence: 99%
“…increased (Ciota et al, 2014). Drakou et al (2020) reported that temperature affects host searching activity of Cx. pipiens, Ae.…”
Section: Introductionmentioning
confidence: 99%
“…From all mentioned parameters above, we must understand that some parameters, especially in the mosquito population, might depend on time or other factors such as weather. For example, mosquitoes are more active when the temperature is low, which means that mosquitoes will be more active in biting humans when the temperature is relatively low [ 40 ]. Based on this explanation, all parameter values in our model as in Table 1 are average values.…”
Section: The Model and Parameter Estimation Resultsmentioning
confidence: 99%
“…The effect of environmental factors on the seasonal abundance and diversity of mosquito varies significantly. The effect of weather parameters on mosquito abundance were reported from across the globe [31,32,33,34,35] . In Assam, mosquito density appeared rising with increasing temperatures and rainfall beginning from March and peak density was reported in April till August [36].…”
Section: Resultsmentioning
confidence: 99%